Dispatches from Latin America: experiments against neoliberalism - Ballve, Teo; Prashad, Vijay (Leftword Books, 2006)
From the laboratory of neoliberalism — popularly known as 'globalization' — Latin America has transformed itself into a launching pad for resistance. As globalization began to spread its devastation, robust and thoughtful opposition emerged in response — in the recovered factory movement of Argentina, in the presidential elections of indigenous leaders and radicals like Chavez and Morales, against the privatization of water in Bolivia. In Dispatches from Latin America, 28 authors report on 11 different countries, together mapping the contemporary political and social terrain. This collection offers us a riveting series of accounts that bring new insight into the region's struggles and victories.